Adaptation in a changing climate: The phenology of two closely related sympatric Ficus species in Taiwan - Yun-Peng Chiang (National Taiwan University, 2021)
Climate change affects precipitation patterns and seasonal temperatures and disrupts the development and distribution of organisms. In the obligate mutualism between Ficus trees (Moraceae) and ﬁg wasps (Hymenoptera: Agaonidae), the trees live mostly in the tropics and rely on short-lived pollinators, and climate change challenges this relationship. In this study, a 25-month phenological survey of Ficus subpisocarpa and Ficus caulocarpa, closely related sympatric Ficus species with different suitable development areas, was conducted in tropical southern Taiwan. The effects of temperature-related meteorological factors were analyzed and compared with data obtained previously for trees in northern Taiwan to identify possible phenological trends caused by climate change. The results revealed that the phenological characteristics of the two Ficus in southern Taiwan are similar to those in northern Taiwan; however, the trees exhibited stronger correlations with meteorological factors in northern Taiwan. In southern Taiwan, the onset of fig crops for the two species was not related to any meteorological variable, and the trees produced figs throughout the year. The leaf changing in southern Taiwan followed no seasonal pattern, and only the renewal of leaves in F. subpisocarpa trees was linked to seasonal increases in temperature. The lowest temperature in northern Taiwan might effect F. subpisocarpa and F. caulocarpa trees to drop their leaves at the same period. Fig trees are likely resilient to climate change and can maintain their mutualism in a warming climate in the near future.